The relationship between the engagement in meaningful activities and health status among elderly in the community - Rosely, Nursafia Najwa; Dahlan, Akehsan (Universiti Teknologi Mara Cawangan Pulau Pinang, 2025)
Engagement in meaningful activities is associated with better physical and mental health among elderly individuals in the community. Such participation may delay age-related decline, reduce mortality, and minimise the need for long-term care. This study examined the relationship between engagement in meaningful activities and health status among community-dwelling elderly. A total of 134 participants aged 60 years and above completed the Engagement in Meaningful Activities Survey (EMAS-12) and the Short Form Health Survey (SF12) using a cross-sectional design. Findings showed a moderate level of engagement, with significant positive correlations for physical health (r = 0.20, p = 0.02) and mental health (r = 0.24, p < 0.01). Group comparisons indicated significant differences in engagement based on education level (F = 11.88, p < 0.001), prior occupation (F = 5.29, p < 0.001), community participation (t = 3.28, p < 0.001), and geographic location (F = 3.67, p = 0.02). Higher engagement was reported among those with tertiary education, professional work backgrounds, active community involvement, and urban residence. In contrast, no significant differences were observed for gender, income, marital status, living arrangement, or ethnicity. Overall, the findings highlight those meaningful activities play a vital role in elderly health, and demographic factors must be considered when designing programmes to promote active ageing and well-being.